2008
DOI: 10.1007/s00405-008-0825-3
|View full text |Cite
|
Sign up to set email alerts
|

New strategies for high precision surgery of the temporal bone using a robotic approach for cochlear implantation

Abstract: The aim of the study was to demonstrate a collision-free trajectory of an instrument through the facial recess to the site of planned cochleostomy guided by a surgery robot. The indication for cochlear implantation is still expanding toward more substantial residual hearing. A cochleostomy as atraumatic as possible will influence the preservation of inner ear function. The employment of a highly precise instrument guidance using a robot could represent a feasible solution for a constant reproducible surgical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 23 publications
0
25
0
3
Order By: Relevance
“…If surgery is to be successful, it is important to perform the cochleostomy in the right position (implantation being impossible otherwise). According to Adunka et al [3,8] the right position for proper cochleostomy is inferior or inferior-anterior to the round window. In our clinic we consider the proper position of the cochleostomy as to be anterior and inferior to the round window with involvement of the round window membrane in the cochleostomy.…”
Section: Introductionmentioning
confidence: 99%
“…If surgery is to be successful, it is important to perform the cochleostomy in the right position (implantation being impossible otherwise). According to Adunka et al [3,8] the right position for proper cochleostomy is inferior or inferior-anterior to the round window. In our clinic we consider the proper position of the cochleostomy as to be anterior and inferior to the round window with involvement of the round window membrane in the cochleostomy.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve such accuracy, a robotically assisted procedure which overcomes the inability to precisely position the surgical drill using hand held instruments [5] was suggested [6][7][8][9][10]. The safe and effective conduction of an image guided, robotically assisted DCA procedure, strongly relies on the quality of the surgical plan and the accuracy at which the surgical plan can be registered to the physical patient intraoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…These methods aim to avoid wide mastoidectomies while at the same time targeting the cochlea, for instance at the round window (RW), at an op-timal geometric angle relative to the basal turn. In this context, patient-specific stereotactic templates Labadie et al, 2008] and skull-mounted [Kobler et al, 2012;Kratchman et al, 2011] or more conventional image-guided robotic approaches [Baron et al, 2010;Klenzner et al, 2009] have been presented. Our group recently demonstrated that a DCA tunnel (1.8 mm in diameter) could be drilled with a targeting accuracy of 0.15 ± 0.08 mm using an image-guided robotic system [Bell et al, 2013].…”
Section: Introductionmentioning
confidence: 99%